Novel Inhibitors and Activity-Based Probes Targeting Trypsin-Like Serine Proteases - Ferguson, Timothy E. G.; Reihill, James A.; Martin, S. Lorraine; Walker, Brian (Frontiers in Chemistry, 2022)
The trypsin-like proteases (TLPs) play widespread and diverse roles, in a host of physiological and pathological processes including clot dissolution, extracellular matrix remodelling, infection, angiogenesis, wound healing and tumour invasion/metastasis. Moreover, these enzymes are involved in the disruption of normal lung function in a range of respiratory diseases including allergic asthma where several allergenic proteases have been identified. Here, we report the synthesis of a series of peptide derivatives containing an N-alkyl glycine analogue of arginine, bearing differing electrophilic leaving groups (carbamate and triazole urea), and demonstrate their function as potent, irreversible inhibitors of trypsin and TLPs, to include activities from cockroach extract. As such, these inhibitors are suitable for use as activity probes (APs) in activity-based profiling (ABP) applications.